EARLY AND LATE SIGNS OF BIOLOGICAL DEATH OBSERVED IN CORPSES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Understanding the early and late signs of biological death is crucial for forensic investigations, medical examinations, and legal proceedings. Early signs, such as rigor mortis and livor mortis, provide insights into the time of death, while late signs, like putrefaction and skeletonization, help determine the postmortem interval (PMI). This article reviews the physiological and biochemical changes that occur after death, explores methods for detecting these changes, and discusses their importance in forensic pathology.